Use of addressing forms to express informality in English and Vietnamese. M.A. Thesis Linguistics : 60 22 15 - Trịnh, Thị Việt Hương (ĐHNN, 2017)
This research aims to study the addressing forms to express informality in English and Vietnamese. Address forms are the terms people use to address the person they are talking to. Its use depends on the relationship and the relative status of individuals (...)